2019
DOI: 10.3390/bs9120123
|View full text |Cite
|
Sign up to set email alerts
|

Do Students Really Use Internet Access for Learning in the Classroom?: Exploring Students’ Cyberslacking in an Indonesian University

Abstract: University students, as ‘digital natives’, use the internet for learning in the classroom. However, the availability of internet access in the classroom becomes a challenge, because students also engage in non-academic internet access during lectures. The use of the internet during lectures for non-academic purpose is called cyberslacking. Self-regulated learning (SRL) and media multi-tasking efficacy (MME) are considered to be important factors contributing to cyberslacking. The participants in this study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Smartphones have become extensively used in our daily lives as smartphone technologies have advanced, making our lives more comfortable. Technostress (Upadhyaya, 2021 ; Wang et al, 2020 ; Qi, 2019 ), problematic smartphone use (Forster et al, 2021 ; Romero-Rodríguez et al, 2020 ; Pereira et al, 2020 ; Eichenberg et al, 2019 ; Wang et al, 2015 ), smartphone addiction, nomophobia (Essel et al, 2021 ; Márquez-Hernández et al, 2020 ; Moreno-Guerrero et al, 2020; Bartwal & Nathan, 2020 ; Jilisha et al, 2019 ; Aguilera-Manrique et al, 2018 ), cyberbullying (Abaido, 2020 ; Chan et al, 2020 ; Wang et al, 2019 ; Peled, 2019 ), and cyberslacking (Sharma, 2020 ; Simanjuntak et al, 2019 ; Rana et al, 2019 ) have all emerged due to the widespread use of smartphones. This study aimed to determine the nomophobic behaviours, the anxiety of being without mobile phone contact (SecurEnvoy, 2012), and variables influencing the nomophobia levels of preservice teachers in five Ghanaian colleges of education.…”
Section: Discussion Limitations and Recommendationsmentioning
confidence: 99%
“…Smartphones have become extensively used in our daily lives as smartphone technologies have advanced, making our lives more comfortable. Technostress (Upadhyaya, 2021 ; Wang et al, 2020 ; Qi, 2019 ), problematic smartphone use (Forster et al, 2021 ; Romero-Rodríguez et al, 2020 ; Pereira et al, 2020 ; Eichenberg et al, 2019 ; Wang et al, 2015 ), smartphone addiction, nomophobia (Essel et al, 2021 ; Márquez-Hernández et al, 2020 ; Moreno-Guerrero et al, 2020; Bartwal & Nathan, 2020 ; Jilisha et al, 2019 ; Aguilera-Manrique et al, 2018 ), cyberbullying (Abaido, 2020 ; Chan et al, 2020 ; Wang et al, 2019 ; Peled, 2019 ), and cyberslacking (Sharma, 2020 ; Simanjuntak et al, 2019 ; Rana et al, 2019 ) have all emerged due to the widespread use of smartphones. This study aimed to determine the nomophobic behaviours, the anxiety of being without mobile phone contact (SecurEnvoy, 2012), and variables influencing the nomophobia levels of preservice teachers in five Ghanaian colleges of education.…”
Section: Discussion Limitations and Recommendationsmentioning
confidence: 99%
“…A student who has both the skills and ability to engage in multitasking using technology will tend to multitask in social media during online classes. According to Simanjuntak, Nawangsari and Ardi [25], students as "digital natives" perceive the fact that their existing technical skills allow them to access the internet while simultaneously doing online classes. This self-perception is not always true since students tend to overestimate their own capacity and show over-confidence which might lead to cyberslacking.…”
Section: Media Multitasking Efficacy and Cyberslackingmentioning
confidence: 99%
“…32,36,58 In the context of members of the digital generation, or millennials, students are considered to have high confidence in their ability to run several media or non-media activities simultaneously. 25,30,59 This seems to be related to their exposure to various forms of media and technology since early childhood, commonly experienced by members of the digital generation. [59][60][61] These experiences are quite intense, regarding the media multitasking which forms the strong confidence of students that they are capable of performing media multitasking.…”
Section: Social Cognition Theory (Sct) and Online Behaviormentioning
confidence: 99%
“…9,30,36 Students with high confidence on their ability to perform media multitasking have the potential to indulge in academic cyberslacking during class time. 24,25,30,57 Their confidence regarding their skills in media multitasking is observable from their behavior when being present in the class, but at the same time also accessing the internet, chatting with friends, opening social media, or reading news unrelated to the course in progress. 12,24,30,57 A study by Wu 30 found that students with high levels of media multitasking self-efficacy would consider themselves able to perform learning activities well, even though they also simultaneously open social media, such as Facebook, and chat with friends.…”
Section: Social Cognition Theory (Sct) and Online Behaviormentioning
confidence: 99%
See 1 more Smart Citation